Afiksasi nomina dalam bahasa Indonesia - Denistia, K; Rajeg, GPW (Agency for Language Development and Cultivation [Badan Pengembangan dan Pembinaan Bahasa], 2023)
This paper describes noun formation in Indonesian through the affixation process. We collected the data from the corpus of Contemporary Indonesian Grammar, which consists of around 18 million words. This paper employs both qualitative and quantitative methodologies. We describe noun formation by examining the underlying forms’ form, meaning, and word class. Furthermore, we analyze the productivity of each noun-forming affix, examine the development of affix productivity per year, and the distribution of word class of the base word for the five most productive noun-forming affixes: -an, ke-/-an, peN-, peN-/-an, and per-/-an. Using the corpus approach, we found new meanings created from the formation of nouns through the affixation process in Indonesian. The data shows that the affixes ke-/-an, peN-/-an, and -an are the most productive noun-forming affixes compared to other affixes. The quantitative approach also allows us to describe the word-class preferences of noun-forming affixes. Our findings indicate that the affix ke-/-an tends to be derived from the adjective word, the affix per-/-an has an over-representation for noun-based words, and verbs have an over-representation as a base word for the affixes -an peN-, and peN-/-an. This research implies benefits in applying corpus, quantitative, and qualitative linguistics methodologies in derivational morphology.